EMBEDDED SYSTEMS AND ITS PIVOTAL APPLICATIONS IN ROBOTICS - Chaitali Pawar Shivani Rokade & Shruti Tapare (International Journal of Research Science and Management, 2017)
We are entering into world of robotics. For something as great as robotics field to be evolved, its assimilation and education is pivotal. When coming towards the robotics platform by learning its key aspects we can develop the robotics to far more extent. This field is linked to many technologies coming up and one of them which is rising up these days is embedded systems. Embedded system is nothing but hardware that is programmed according to one’s need for real time computing. Here we present a study of embedded systems involved in robotics. Any Robot is merely a hardware that is made functional by using programming in software which is later interfaced with hardware. In these two contiguously growing technology where one bolsters the other, ideas can be implemented to suffice the increasing demand for it. Robots have always had an advantage over humans of preciseness, speed and work capacity. Henceforth, its study comes in the picture, which is presented here. How a technique is better or can be improvised in embedded systems and inherited in robotics is mentioned here. A review of systems is stated so as to intact the study all in one.